2008
DOI: 10.3133/ofr20081365
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring inland storm surge and flooding from Hurricane Ike in Texas and Louisiana, September 2008

Abstract: The U.S. Geological Survey (USGS) deployed a temporary monitoring network of 117 pressure transducers (sensors) at 65 sites over an area of about 5,000 square miles to record the timing, areal extent, and magnitude of inland hurricane storm surge and coastal flooding generated by Hurricane Ike, which struck southeastern Texas and southwestern Louisiana September 12-13, 2008. Fifty-six sites were in Texas and nine were in Louisiana. Sites were categorized as surge, riverine, or beach/wave on the basis of proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Post‐storm data collected on 18 September 2008 indicated that significant coastal change occurred over the entire peninsula due to primarily inundation processes. Water levels at multiple locations observed by USGS water level gauges deployed in advance of the storm [ East et al , ] showed that water level ( R low ) peaked at 4.3 m on the ocean side of Bolivar Peninsula. NDBC buoy 42035 near Galveston, Texas, recorded a maximum significant wave height of 6 m before going adrift [ Doran et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…Post‐storm data collected on 18 September 2008 indicated that significant coastal change occurred over the entire peninsula due to primarily inundation processes. Water levels at multiple locations observed by USGS water level gauges deployed in advance of the storm [ East et al , ] showed that water level ( R low ) peaked at 4.3 m on the ocean side of Bolivar Peninsula. NDBC buoy 42035 near Galveston, Texas, recorded a maximum significant wave height of 6 m before going adrift [ Doran et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…These instruments included Gauge Y, which was located directly offshore of the Bolivar Peninsula. Additional water level data was available from USGS rapidly-deployed surge gauges (East et al, 2008). Of these, gauges GAL-1 and GAL-2 were on the open coast of the Gulf of Mexico, and 2.1km inland at the Gulf Intracoastal Waterway (GIWW), respectively.…”
Section: Surements Of Forerunner Surgementioning
confidence: 99%
“…The region of interest is broadly defined using NOAA's meteorological forecasts of the hurricane track and its uncertainty. Guided by forecast information, USGS successfully deployed storm surge sensors at 59 locations along the coast, including beach, inland, and riverine settings [East et al, 2008]. NOAA's existing analysis of hurricane scenarios and numerically simulated surge elevations ("maximum of the maximum" surge, or MOMS) for hurricane categories 1-5 were used to characterize storm surge threats in the region of interest.…”
Section: Hurricane Ike: Scenario-based Predictionsmentioning
confidence: 99%
“…Recovery of USGS in situ storm surge sensors took place in the week after landfall [East et al, 2008]. Figure 2d compares the probabilistic (10% exceedence) storm surge prediction with the observations.…”
Section: Updated Observationsmentioning
confidence: 99%